Glucose Metabolism Reprogramming of Regulatory T Cells in Concanavalin A-Induced Hepatitis - Huang, Chen; Shen, Yi; Shen, Mengyi; Fan, Xiaoli; Men, Ruoting; Ye, Tinghong; Yang, Li (Frontiers in Pharmacology, 2021)
Autoimmune hepatitis (AIH) is an inflammatory liver disease caused by a dysregulated immune response. Although the pathogenesis of AIH remains unclear, impaired regulatory T cells (Tregs) have been considered a driver of AIH development. Unlike autoreactive T cells, Tregs mainly utilize oxidative phosphorylation (OXPHOS) as their energy supply. Elevated glycolysis has been reported to limit the suppressive functions of Tregs. However, whether glucose metabolism reprogramming in Tregs is involved in AIH etiology remains unknown. The aim of this study was to examine alternations in Treg numbers and functions in AIH patients and concanavalin A (Con A)-induced hepatitis, while exploring associations between impaired Tregs and glucose metabolism. The frequency of Tregs was decreased in the peripheral blood but increased in liver biopsies of AIH patients. Moreover, immunosuppressive therapy rescued circulating Tregs in AIH. In Con A-induced immune hepatitis, enhanced intrahepatic Treg accumulation was observed over time, accompanied by reduced splenic Treg numbers. To investigate whether functional impairment of Tregs occurs in AIH, Tregs were isolated from experimental AIH (EAH) model mice and normal controls and the former displayed downregulated mRNA levels of FOXP3, CTLA4, CD103, TIGIT, CD39, and CD73. EAH model-derived Tregs also produced fewer anti-inflammatory mediators (TGF-β and IL-35) than control Tregs. Moreover, enhanced glycolysis and reduced OXPHOS were found in Tregs from EAH model mice, as reflected by elevated levels of key glycolytic enzymes (HK2, PK-M2, and LDH-A) and a decreased ATP concentration. This study revealed a decreased peripheral Treg frequency and abnormal intrahepatic Treg infiltration in AIH. It is first reported that glucose metabolism reprogramming is associated with decreases and functional impairments in the Treg population, promoting AIH development. Targeting glucose metabolism may provide novel insights for the treatment of AIH.